Prevalence of Upper Gastrointestinal Symptoms and Gastric Dysrhythmias in Diabetic and Non-Diabetic Indian Populations: A Real-World Retrospective Analysis from Electrogastrography Data - Bandyopadhyay, Sanjay; Kolatkar, Ajit (Diagnostics (Basel), 2025)
Background: Upper gastrointestinal (GI) motility disorders, such as gastroparesis and functional dyspepsia (FD), contribute significantly to morbidity, especially in populations at risk for type 2 diabetes. However, the prevalence and clinical manifestations of these disorders in India, and associated gastric dysrhythmias, are not well studied within this population. Methods: This retrospective, cross-sectional study analyzed 3689 patients who underwent electrogastrography with water load satiety test (EGGWLST) testing across multiple motility clinics in India. The prevalence of gastroparesis and FD-like symptoms, symptom severity, and their association with diabetes and other comorbidities were evaluated. Symptom severity was assessed using the Gastroparesis Cardinal Symptom Index (GCSI). EGGWLST findings were documented, including the gastric myoelectric activity threshold (GMAT) scores. Results: The study population had a mean age of 43.18 years. GCSI scores indicated that patients had symptoms that were mild (55%), moderate (33%), and severe (8%). Compared with the non-diabetic population, diabetic subjects had significantly higher rates of early satiety (56% vs. 45%, p < 0.0001), bloating (73% vs. 67%, p = 0.005), and reflux (28% vs. 24%, p = 0.029). WLST data analysis revealed that significantly more diabetic subjects ingested <350 mL (16% vs. 12%, p = 0.000016). EGG analysis revealed gastric dysthymias in one-third (65%) of patients. Significantly more diabetic subjects (22% vs. 18% p = 0.015) had a GMAT score >0.59. Conclusions: Upper GI motility disorders are prevalent in India, particularly among diabetic patients. EGG is a valuable tool for characterizing these disorders, and may help in personalizing therapeutic approaches. Further research is required to optimize treatment strategies.